Heat-Resistant Composite Coating with A Fluidized Bed of the Under-Reactor Melt Trap of A Light-Water Nuclear Reactor - Bekmuldin M. K. Maksat Kuatbekovich; Skakov M. K. Mazhyn Kanapinovich; Baklanov V. V. Viktor Vladimirovich; Akaev A. S. Asan Sabyrovich; Gradoboev A. V. Aleksandr Vasilyevich (2021, 2021)
Title screen